Method Of Planting Religious Moderation Values In Islamic Religious Education Learning For Students At SMAN 2 Luwuk, Banggai Regency, Central Sulawesi - Djibran, Agung Kurniawan (IJGIE (International Journal of Graduate of Islamic Education), 2025)
Having a moderate nature means not being fanatical, especially to the point of blind fanaticism that always considers others to be wrong. This excessive attitude can trigger the occurrence of religious conflicts that will threaten the sovereignty of the nation. The values of religious moderation among students are only understood by a few students at SMAN 2 Luwuk. SMAN 2 Luwuk continues to strive to instill the values of religious moderation through learning in shaping students who have a harmonious attitude and mutual respect. The results of the study show that the values of religious moderation instilled in Islamic Religious Education learning at SMAN 2 Luwuk are the values of tawassuth, tasamuh or tolerance, fairness, nationalism, unity, equality, and muwatanah. Meanwhile, the methods of planting the values of religious moderation in Islamic Religious Education learning are through exemplary, habituation, and guidance.